2019
DOI: 10.1016/j.heliyon.2019.e02382
|View full text |Cite
|
Sign up to set email alerts
|

Internal parasitic burdens in brown rats (Rattus norvegicus) from Grenada, West Indies

Abstract: This study identified the endoparasites in Brown rat ( Rattus norvegicus) during May to July 2017 in Grenada, West Indies. A total of 162 rats, 76 females and 86 males were trapped from St. George and St. David parishes in Grenada. The collected fecal samples were examined for parasitic eggs and/or oocysts using simple fecal flotation technique. Adult parasites found in the intestinal tract were examined for identification. The overall prevalence of intestinal parasites among rats was 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Comparing the prevalence rates with other countries, the prevalence of 33.3% is higher than in 13.9% in Pakistan (Ahmad et al, 2014) but lower than in Brazil and in Grenada (Indies), where rates of 73.6% and 79% were reported (Coomansingh-Springer et al, 2019;Lima et al, 2021) These variations may be attributed to differences in the level of sanitation between the study sites and local ecological conditions influencing the epidemiology of parasites (Shah-Fischer & Say, 1989). Another study in Pakistan reported similar results with a prevalence of 33.3% (Garedaghi & Khaki, 2014) .…”
Section: Discussionmentioning
confidence: 82%
“…Comparing the prevalence rates with other countries, the prevalence of 33.3% is higher than in 13.9% in Pakistan (Ahmad et al, 2014) but lower than in Brazil and in Grenada (Indies), where rates of 73.6% and 79% were reported (Coomansingh-Springer et al, 2019;Lima et al, 2021) These variations may be attributed to differences in the level of sanitation between the study sites and local ecological conditions influencing the epidemiology of parasites (Shah-Fischer & Say, 1989). Another study in Pakistan reported similar results with a prevalence of 33.3% (Garedaghi & Khaki, 2014) .…”
Section: Discussionmentioning
confidence: 82%
“…No study has evaluated infection of rats with A. cantonensis in Martinique. In neighbouring Grenada [8,10], Puerto Rico [4], Dominican Republic [45], Haiti [40], Jamaica [46], and Cuba [2], the proportion of infected Rattus spp. varies from 23.4% to 60.0% [2,8], while the parasite appears to be absent in rats in Barbados [25].…”
Section: Discussionmentioning
confidence: 99%
“…are the most common helminths found in rats (Amin et al, 2019;Coomansigh-Springer et al, 2018;Lima et al, 2021). For comparison, helminths recorded the most endoparasites found in wild rats as protozoa (Coomansingh-Springer et al, 2019). Earlier studies revealed that oil palm estate workers in plantation areas were also potentially infected by common helminth species, H.diminuta and H.nana (Sinniah et al, 1978).…”
Section: Background Of Studymentioning
confidence: 99%